1999
DOI: 10.1152/ajpheart.1999.276.2.h376
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cAMP to adenosine: role in vasodilation of rat pial artery in response to hypotension

Abstract: The purpose of this experiment was to examine whether the cAMP-adenosine pathway is implicated in the autoregulatory vasodilation in response to hypotension. Suffusion with cAMP (1–100 μmol/l) or adenosine (0.01–10 μmol/l) caused a sustained vasodilation of the resting pial arteries in a concentration-dependent manner. In contrast, N 6,2′- O-dibutyryl-cAMP and 8-bromo-cAMP exerted a weak dilation at high concentration (100 μmol/l). The vasodilation to cAMP (1–100 μmol/l), adenosine (0.01–10 μmol/l), and hypote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The myocyte-derived adenosine is a key substance in autoregulation of the coronary arterial system (11,12,19,43). Adenosine may play similar crucial roles in the autoregulatory function of the aortic (5), cerebral (14), and renal vasculature (17). Recently, it was reported that cultured pulmonary arterial endothelial cells endogenously produce ATP in response to shear stress and that endogenous release of ATP plays a significant role in the regulation of functions of cultured endothelial cells (47).…”
Section: ϫ7mentioning
confidence: 99%
“…The myocyte-derived adenosine is a key substance in autoregulation of the coronary arterial system (11,12,19,43). Adenosine may play similar crucial roles in the autoregulatory function of the aortic (5), cerebral (14), and renal vasculature (17). Recently, it was reported that cultured pulmonary arterial endothelial cells endogenously produce ATP in response to shear stress and that endogenous release of ATP plays a significant role in the regulation of functions of cultured endothelial cells (47).…”
Section: ϫ7mentioning
confidence: 99%
“…50 Further it has been shown that inhibition of ADK increases cerebral blood flow (CBF) by augmenting interstitial adenosine levels. 56 In addition, chronically increased levels of adenosine have been shown to stimulate angiogenesis 1,29,49 Consequently, chronic overexpression of ADK, as seen in epilepsy, may result in reduced CBF and reduction of local vasculature. Therefore, ADK-dependent changes in vasculature might provide a diagnostic opportunity for the detection of an epileptogenic focus that is characterized by overexpression of ADK.…”
mentioning
confidence: 99%
“…Significant increases in extracellular adenosine levels occur with concentrations of cAMP in the medium as low as 1 M, and steady-state levels of adenosine are achieved in the culture medium within 5 min after adding exogenous cAMP. In addition to aortic vascular smooth muscle cells and cardiac fibroblasts, the extracellular cAMPadenosine pathway is present in hepatocytes (Gorin and Brenner, 1976;Smoake et al, 1981), neurons (Rosenberg and Dichter, 1989;Rosenberg et al, 1994;Li, 1995, 1996;Brundege et al, 1997), adipocytes (Kather, 1990;Zacher and Carey, 1999), isolated perfused kidneys Jackson, 1995, 1998), cerebral blood vessels (Hong et al, 1999), renal microvessels , collecting ducts , and proximal tubules (Jackson et al, 2006). However, whether the extracellular cAMP-adenosine pathway accounts for a significant portion of adenosine biosynthesis in vivo is unknown and is the focus of the present investigation.…”
mentioning
confidence: 99%